2008
DOI: 10.1038/clpt.2008.177
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Sildenafil in Term Neonates: Evidence of Rapid Maturation of Metabolic Clearance in the Early Postnatal Period

Abstract: The phosphodiesterase 5 inhibitor sildenafil is a potential therapeutic option in the treatment of persistent pulmonary hypertension of the newborn (PPHN) and neonatal hypoxemia. In this open-label trial, 36 term neonates with PPHN or hypoxemia were administered intravenous sildenafil for up to 7 days starting within 72 h of birth. A mixed-effects pharmacokinetic model that included two-compartment disposition of sildenafil and its metabolite and an effect of postnatal age on sildenafil clearance was used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 28 publications
6
101
0
1
Order By: Relevance
“…Either iNO or endotracheal rhSOD decreased PDE5 activity and restored normal postnatal levels of cGMP (44). These data are concordant with the observation that ROS may compromise GC activity (161) and activate PDE5 expression (45, 106), while rhSOD would prevent such detrimental effects and are also in agreement with clinical studies indicating the usefulness of PDE5-inhibitors, as Sildenafil, in the treatment of PPHN (105,163). A recent study also reported that cyclic stretch is associated with increased OS in pulmonary artery smooth cells along with increased GC expression (151).…”
Section: Newborn Lung Polymorphisms Antioxidant Enzymessupporting
confidence: 78%
“…Either iNO or endotracheal rhSOD decreased PDE5 activity and restored normal postnatal levels of cGMP (44). These data are concordant with the observation that ROS may compromise GC activity (161) and activate PDE5 expression (45, 106), while rhSOD would prevent such detrimental effects and are also in agreement with clinical studies indicating the usefulness of PDE5-inhibitors, as Sildenafil, in the treatment of PPHN (105,163). A recent study also reported that cyclic stretch is associated with increased OS in pulmonary artery smooth cells along with increased GC expression (151).…”
Section: Newborn Lung Polymorphisms Antioxidant Enzymessupporting
confidence: 78%
“…215 Sildenafil clearance in the early neonatal period is low as a result of the relative immaturity of the hepatic cytochrome P450 system but rapidly increases during the first week of life. 216 Hypotension can occur during the initial loading infusion but was not observed when the loading dose (0.4 mg/kg) was delivered over 3 hours, followed by a maintenance dose of 1.6 mg·kg…”
Section: Pulmonary Vasodilator Therapymentioning
confidence: 99%
“…19,25 Oral sildenafil displays an adequate bioavailability (23% in male rats and 38% in humans). 60,61 Sildenafil is metabolized faster in male rats compared with humans, with the elimination half-life of, respectively, 0.4 and 3.7 hours after an oral administration. 61 Dosages in the present study were chosen so that they correspond somewhat to the equivalent recommended amount for human newborns ranging from low doses that are usually initially used to maximal described doses.…”
Section: Discussionmentioning
confidence: 99%